(untitled) (Fiep Bulletin - online, 2012)
Epidemiological studies conducted recently found changes in lifestyle and eating habits in the past decades. So individuals have given great importance to their quality of life, resulting in an increased demand for customized training, which is a form of training which may vary according to interests, goals, previous experiences and initial levels of fitness. Thus, keeping in view the growth of approximately 25% of demand for personal training per year and the benefits gained from the practice of that activity, the present study possessed the main objective to analyze the influence of a customized training program on body composition of adults. We analyzed 12 patients entering a systematic program of personal training at a gym in the city of Maringá - PR. With the results obtained that the female population had increased weight, BMI, TF, LM, and a reduction in rates of BF% and WHR. Since the male population increased by MM and WHR, the values of weight, BMI,% BF and TF reduced when compared to the first assessment. No significant differences among the analyzed variables. We conclude that a customized program of resistance exercise provides an increase in body weight and BMI and LM, being effective for reducing body fat indexes.